The Influence of Participatory Leader Behaviour, Achievement Orientation and Work Motivation on Teacher Job Satisfaction in Madrasah - Rosnawati, Rosnawati; Latif, Mukhtar; Anwar, Kasful (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study explores the factors influencing teacher job satisfaction in Madrasah Tsanawiyah Negeri (MTsN) in Riau Islands Province. The study focused on participatory leader behaviour, achievement orientation, and work motivation as the main variables affecting teacher job satisfaction. The research method used is quantitative with a statistical analysis approach to test the hypothesis that has been set. Three schools with the same accreditation status (A) in the western, central, and eastern research areas were selected as samples through area sampling techniques. The total sampling technique was used to take 136 teachers from these schools. The results showed that participatory leader behaviour and achievement orientation significantly influenced teacher job satisfaction directly or indirectly through work motivation. The pathway analysis confirmed that participatory leader behaviour, achievement orientation, and work motivation significantly affected teacher job satisfaction in MTsN in Riau Islands Province. The implication is to develop effective and holistic management strategies to improve the welfare of educational organizations.